Assessment of occupational injury and illness risks for the position of mineral water warehouse forklift operator - Anișoara Habuc; Claudiu Babiş; Elena Anda Botoc; George Mit; Andrei Dimitescu (Journal of Research and Innovation for Sustainable Society)
Optimizing the work accident and/or occupational disease prevention activity has as its starting point the assessment of occupational injury and disease risks. The notion of risk is defined in specialized literature by the probability with which an accident or an occupational illness occurs in a work process with a certain frequency and severity of consequences. The purpose of assessing the level of risk is to offer the possibility of knowing the real situation at each workplace, from the point of view of work security, in order to take the most suitable preventive measures for the given situation. The basis of the risk assessment principle consists in taking into account two parameters: the frequency of accidents and the severity of the maximum foreseeable consequence (principles also included in European standards).